2010
DOI: 10.3171/2009.4.spine0876
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic ectopic bone formation after off-label use of recombinant human bone morphogenetic protein-2 in transforaminal lumbar interbody fusion

Abstract: Object Recombinant human bone morphogenetic protein-2 (rhBMP-2) has been approved for use in the lumbar spine in conjunction with the lumbar tapered cage. However, off-label use of this osteoinductive agent is observed with anterior fusion applications as well as with both posterior lumbar interbody fusion and transforaminal lumbar interbody fusion (TLIF). Complications using rhBMP-2 in the cervical spine have been reported. Although radiographic evidence of ectopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 30 publications
0
76
0
Order By: Relevance
“…36 We have previously shown that BMP genemodified MSCs secrete physiological quantities (nanograms) of BMP 28,34 over a period of few weeks compared to the mega doses used in rhBMP therapy (milligrams). Thus, the use of gene-modified MSCs might prevent recently described toxic side effects and inflammatory response induced by high doses of BMP 11,12 . In addition, gene modification could be applied to freshly isolated, noncultured MSCs 37 without the need for a cell culture phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 We have previously shown that BMP genemodified MSCs secrete physiological quantities (nanograms) of BMP 28,34 over a period of few weeks compared to the mega doses used in rhBMP therapy (milligrams). Thus, the use of gene-modified MSCs might prevent recently described toxic side effects and inflammatory response induced by high doses of BMP 11,12 . In addition, gene modification could be applied to freshly isolated, noncultured MSCs 37 without the need for a cell culture phase.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Another widely used treatment includes the implantation of metal cages containing recombinant bone morphogenetic protein-2 (BMP-2). Highdose recombinant human BMP-2 (rhBMP2) has been found to cause pseudarthroses, 8,9 various infections, 10 ectopic bone formation that cause neural compression, 11 and abdominal bone growth. 12 In osteoporotic compression fractures of the spine, the use of instrumental fixation to achieve spinal fusion has a high failure rate due to low bone mass; when this procedure is combined with vertebral augmentation involving biomaterials such as poly(methyl methacrylate) (PMMA), a significant modulus mismatch with adjacent vertebrae may occur, leading to increased stress at the augmentednonaugmented junction.…”
Section: Introductionmentioning
confidence: 99%
“…28 While BMPs have successfully induced bone formation in vivo, high dose requirements and paradoxical activities of BMPs on progenitor cells may lead to unexpected side effects such as ectopic bone formation while also rendering high treatment costs to patients. [5][6][7][8] In this study, we employed a small molecule that can effectively complement the pro-osteogenic activity of BMP-2 to maximize biological efficiency, thereby reducing the total dose requirement (cost) and minimizing potential adverse effects associated with BMP-2. Small molecular therapeutics has several advantages over protein-based therapeutics due to their lower cost and ease of manufacturing and storage compared with growth factor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, along with high cost, application of such high doses has revealed numerous side effects, such as vertebral osteolysis with cyst formation and life-threatening inflammatory cervical swelling, which have been well documented. [5][6][7][8] Thus, there is a need to develop alternative osteoinductive molecular strategies that can effectively complement BMP activity to maximize biological efficiency while reducing BMP dose requirement. One alternative approach is to deliver small molecule compounds targeting osteoblast differentiation that can synergistically promote bone formation with BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Joseph et al reported a 20.8 % rate of heterotopic bone formation with rhBMP-2 compared with 8.3 % in the controls following an MIS-TLIF [37]. Similarly, Chen et al reviewed 147 patients who underwent an MIS-TLIF and reported that 10.8 % (4 out of 37 patients) of patients who received rhBMP-2 developed ectopic bone formation in the spinal canal and neuroforamen that resulted in delayed neural complaints after the initial resolution of clinical symptoms [38].…”
Section: Neuroforaminal Bone Formationmentioning
confidence: 99%